RANCANG BANGUN PROTOTIPE SISTEM KENDALI JEMBATAN PINTAR BERBASIS ARDUINO UNTUK MONITORING OPERASIONAL OTOMATIS SECARA REAL-TIME - Glenn Andesta; Nada Savaira; Najwa Azzahra; Rangga Saputra; Ratna Atika (JURNAL TELISKA, 2026)
The growth of water and land transportation traffic in Indonesia often causes conflicts on conventional bridges, especially in river areas frequently crossed by large vessels. This condition has the potential to cause accidents and disrupt traffic mobility. This study aims to design and implement a smart bridge control system based on Arduino Uno that can operate automatically to improve the safety and efficiency of lift bridge operations. The research employed a Research and Development (R&D) approach with a prototype method. The system utilizes Arduino Uno as the main microcontroller, HC-SR04 ultrasonic sensor to detect ships, SG90 servo motors as actuators for driving the bridge and barrier gates, along with a 16x2 LCD, traffic light module, and buzzer as indicators. The bridge opening and closing process is controlled automatically with a programmed safety sequence. The test results show that the system is able to detect vessels, provide early warnings, close the barrier gates, lift the bridge, and automatically return to normal conditions with good response. This system successfully minimizes human error and provides real-time information to road users through the LCD display and traffic lights.